Hydrogen sulfide alleviates high-salt-stimulated myocardial fibrosis through inhibiting hypoxia-inducible factor-1α - Peng, Qian; Huang, Pan; Lv, Boyang; Tang, Chaoshu; Jin, Hongfang; Huang, Yaqian (Frontiers in Pharmacology, 2025)
BackgroundEndogenous hydrogen sulfide (H2S) and its key generating enzyme, cystathionine β-synthase (CBS), prevent vascular remodeling and damage to target organs during the advancement of hypertension induced by a high-salt diet.ObjectiveThe contribution of the H2S/CBS pathway to high-salt–induced myocardial fibrosis (MF) was explored, with a focus on the mechanistic involvement of hypoxia-inducible factor-1α (HIF-1α).MethodsWe used primary rat cardiac fibroblasts stimulated with high-salt medium and an MF model induced by a high-salt diet in Dahl salt-sensitive rats. Sodium hydrosulfide (NaHS), a commonly used H2S donor, was administered in vitro at 100 μmol/L and in vivo at 90 μmol/kg to maintain adequate H2S levels. An HIF-1α stabilizer, dimethyloxalylglycine (DMOG), was used to maintain the HIF-1α protein level. The H2S/CBS pathway was followed using Western blotting and a sulfide-sensitive probe. The extent of MF was examined using histological and immunofluorescence staining techniques, including Sirius red and Masson trichrome. We performed Western blot analysis to measure fibrosis-related protein and HIF-1α protein levels.ResultsHigh-salt exposure reduced H2S production and downregulated CBS protein expression in cardiac fibroblasts both in vitro and in vivo. In vitro, the H2S donor inhibited the activation of cardiac fibroblasts triggered by high-salt conditions, while in vivo, it alleviated MF in salt-sensitive rats. From a mechanistic standpoint, high-salt exposure markedly upregulated HIF-1α expression. However, this increase was reversed by pretreatment with H2S. Furthermore, the HIF-1α stabilizer DMOG blocked the H2S-induced reduction in HIF-1α protein levels and consequently abolished the antifibrotic effect of H2S on cardiac fibroblasts exposed to high-salt conditions.ConclusionIn conclusion, H2S attenuates high-salt-induced MF by suppressing fibroblast activity and collagen synthesis, potentially via downregulation of HIF-1α.